Generalized Gross-Neveu Universality Class with Non-Abelian Symmetry - Gracey, John A. (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
We use the large critical point formalism to compute -dimensional critical exponents at several orders in 1/ in an Ising Gross-Neveu universality class where the core interaction includes a Lie group generator. Specifying a particular symmetry group or taking the abelian limit of the final exponents recovers known results but also provides expressions for any Lie group or fermion representation.